Local Defence Volunteers, 1940 (Wimbeldon, 1940)
1940 1939-1945 "Local Defence Volunteers, 1940" [HFR0039], 1940 In May 1940, when invasion seemed a real possibility, the Government called for the recruitment of Local Defence Volunteers in every town and village. When Winston Churchill raised the status of the force and renamed it the Home Guard in September 1940, it already had 1.5 million members. Recruitment peaked at 1.8 million in March 1943 and never fell below 1 million until the Home Guard was disbanded in December 1945. Factories, railways and other large concentrations of workers had their own units to defend their own buildings and workforce. This unpaid civilian army came under military law and discipline. From January 1942, the Ministry of Labour could direct men to enrol in areas where units were below strength.